Gender classification from face images using support vector machine - Phyu Phyu Thant. (2008)
Investigated the performance of support vector machine on gender categorization using images. Radial Basic Kernel and two parameters of the RBF kernel were chosen. By using random selection of images for training the classifier in a series of runs, the accuracies were determined.